'Trifecta' after radical prostatectomy: is there a standard definition?. (11th June 2013) - Borregales, Leonardo D.; Berg, William T.; Tal, Oded; Wambi, Chris; Kaufman, Sarah; Gaya, Jose M.; Urzúa, Cristian; Badani, Ketan K.
<x xml:space="preserve">Abstract</x> Objectives To determine the extent of variability in the definitions of the 'trifecta' after radical prostatectomy (undetectable PSA, urinary continence and potency) to be found in the literature. To establish a consensus definition of the trifecta in an effort to standardize criteria and reporting. Materials and Methods A systematic review of published articles found in the PubMed database for the period from January 2003 to March 2012 was performed. The search queries included the keywords 'radical prostatectomy, ' 'prostatectomy outcome, ' and 'trifecta'. Results A total of 86 publications were identified of which 14 were used for analysis. Eight different definitions of biochemical recurrence were reported, the most common definition being PSA ≥0.2 ng/mL. The definition of potency was the most variable. Ten different definitions of potency were found, with the most common being 'having erections sufficient for intercourse with or without a phosphodiesterase‐5 inhibitor'. Nine different definitions of continence were found. The most common definition of continence was 'wearing no pads'. Only six of the 14 articles used validated questionnaires in their outcome measures. Conclusions The definitions of trifecta reported in the literature are highly variable. We propose the following consensus definition based on our analysis: (1) PSA >0.2 ng/mL with confirmatory value; (2) attainment of erections sufficient for intercourse with or without oral pharmacological agents; (3) wearing zero pads. This consensus definition should be considered when designing studies and reporting outcomes of radical prostatectomy.